Challenges of Indian MSME Exporters: A Review. Issue 3 (September 2019) - Tripathy, Ishita G.; Kumar, Pawan
The micro, small and medium enterprise (MSME) sector is considered as an engine of economic growth for India. This study aims to make an in-depth review of a few tariff and non-tariff barriers in the destination market to understand factors leading to access of these markets. The study underscores the importance for MSMEs to have access to comprehensive and updated information about their destination markets abroad. This article recommends government support for MSMEs to ensure effective access to destination markets.